Pnaic’s literacy games: contributions and limitations from the teachers’ perpsectives - de Lucca, Tatiana Andrade Fernandes [UNESP]; Osti, Andréia [UNESP]; Parente, Cláudia da Mota Darós [UNESP] (Universidade Estadual de Maringa, 2023)
This article analyses how female literacy teachers who took part in the 2013 National Pact for Literacy at the Correct Age-Pnaic formation understand the contribution of the programme’s games to literacy, discussing the relation there is between inserting the resources in a classroom and the teacher’s formation directed towards this subject. Taking into account the relevance of systematic teaching for linguistic contents, and the researches on the specificities of the educators’ formation, the discussion aimed to relate how the specific formation on PNAIC can foster the understanding of how relevant it is to make use of literacy games. To do so, we carried out a bibliographic and documentary research on the subject, including Pnaic’s formation materials and the games’ analysis. We also interviewed ten female educators who took part in Pnaic, in order to investigate how the discussion on the games took place at the formation and how the teachers evaluated the material. We could infer that it is necessary to invest in formations on playfulness and specifically on the games and their possibilities and limitations in the education context. The participants regard the games as contributing resources for literacy, but point at failures when the subject is discussed at the formation. We reiterate the formation processes need to work as spaces for discussions and reflections of the educators’ actions.
Juegos de alfabetización del PNAIC: contribuciones y limitaciones en las perspectivas de las profesoras
Jogos de alfabetização do Pnaic PNAIC: contribuições e limitações nas perspectivas das professoras
Keywords: educator formation; playfulness; teaching practice